(untitled) (New Jersey, 2003)
This book deals with the latest developments in the area of three-quark systems. Emphasis is given to the discussion of new experimental results in the areas of form factors, unpolarized and polarized structure functions, and baryon structure and spectroscopy. Of particular interest are the new theoretical developments in the area of generalized parton distributions and lattice quantum chromodynamics.
Keywords: Baryons,Trọng tử